State of Corporate Social Responsibility in India – Current scenario, Approach and Drivers - Nagpal, Kshitij (2016)
Purpose – The aim of the study is to examine the state of Corporate Social Responsibility (CSR)in India. The report attempts to investigate the current scenario of CSR ctivities and examine how corporations in India interpret CSR. The study also seeks to identify the reported driving forces behind implementation of CSR practices by firms in India. Methodology – CSR personnel from 3O companies that are obligated to spend on CSR activities under the Companies Act, 2013 were surveyed. To critically evaluate the achieved results through survey,3 semi-‐structured deep experts’interviews were also conducted. Findings – Environment and human resource turned out to be the most common thematic areas where firms in India prefer to direct their CSR initiatives. As far as the mode of implementation of CSR projects is concerned, partnership with NGOs was found to be the most preferred mode of collaborations followed by the mode of collaborations with other companies and government. The result indicated that stakeholder approach is the most adopted approach by the firms in India. Furthermore,results suggest that moral values are the most important driving forces for the firms in India to pursue CSR. Research Limitations/Implication – The focus of the research is on the companies that are obligated under Companies Act, 2013 to spend specific budget on CSR activities. As a result of that,no small and medium size enterprise (SMEs)were considered to be the part of this study. The scope of the study is restricted to the CSR practices of the companies that meet the criterion of Companies Act, 20013. Further research should expand on this effort by conducting comparative studies of SMEs that are engaged in voluntarily CSR initiatives. Original value – The majority of studies conducted in the field of CSR belong to the western part of the world. Studies undertaken in India are rare, and also do not address an important question of what companies are actually doing as a part of CSR. More importantly, only recently CSR in India became a mandate and not many studies consider this crucial transition. The research aims to fill this gap by focusing on emerging economies like India and provide a deep insight to how CSR is being perceived.